Barycentric Rational Collocation Method for Burgers’ Equation - Qingli Zhao; Ruiwen Wang; Zhaoqing Wang; Xiaoping Zhang (Journal of Mathematics)
In this article, barycentric rational collocation method is introduced to solve Burgers’ equation. The algebraic equations of the barycentric rational collocation method are presented. Numerical analysis and error estimates are established. With the help of the barycentric rational interpolation theory, the convergence rates of the barycentric rational collocation method for Burgers’ equation are proved. Numerical experiments are carried out to validate the convergence rates and show the efficiency.